PENGARUH KOMUNIKASI KERJA, KEPEMIMPINAN DAN PELATIHAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT BUMISARI PRIMA MEDAN - Rick Thio Nanda; Ina Namora (Jurnal Bisnis dan Manajemen, 2020)
This research was conducted at PT Bumisari Prima which has long been established and is a leader in the field of starch manufacturing. In this study aims to be able to analyze employee work communication, leadership and employee work training on employee job satisfaction at PT Bumisari Prima. Job satisfaction at this company has decreased due to communication, leadership and job training that has not been optimal. The population is 162 employees of PT Bumisari Prima and the sample is 115 employees of PT Bumisari Prima The research method uses multiple linear regression analysis techniques. The results of the hypothesis testing partially obtained tcount ttable or 2.498 1.982 and significant obtained 0.014 0.05, tcount ttable or 2.337 1.982 and significant obtained 0.019 0.05 and tcount ttable or 2.359 1,982 and significant obtained 0.020 0.05. The results of the simultaneous hypothesis testing obtained F value (10.358) F table (2.69) and the probability value of significance 0.000 0.05. The coefficient of determination test results obtained Adjusted R Square value of 0.198, this means that 19.8% of the variation of the dependent variable is the performance of PT Bumisari Prima employees which can be explained by variations in the independent variables that are free communication, leadership and work training while the remaining 80.2% explained by other variables not examined in this study. The conclusions in this study indicate that simultaneous and partial Work Communication, Leadership and Job Training have a positive and significant effect on Employee Job Satisfaction at PT Bumisari Prima (tapioca flour production).